De kracht van een overtuiging : 60 jaar ACW 1921-1981. - Wils, Lode; Gerard, Emmanuel; Falter, R. (Zele : Reinaert Uitgaven, 1981)
Bibliotheek François Vercammen
Nederlands
Monografie
Keywords: christelijke arbeidersbeweging